Prevalence of Non-Prescribed Drug Use in Hospital Patients Assessed by Urine Toxicology Testing - Bochor, Nada; Doherty, Ronan; Quigley, Ciara; Boran, Gerard (Trinity Student Medical Journal, 2018)
To analyse the results of a survey for non-prescribed drug use in selected patient populations in Tallaght University Hospital to determine the patterns of drug use by urine toxicology testing. Urine toxicology screening results done by the Alere Triage® TOX Drug Screen Meter were extracted from the Clinical Chemistry Lab database from the 5th of March to the 23rd of March at Tallaght University Hospital. Results were analysed to determine which drug tested positive most commonly. Benzodiazepines were the most prevalent drugs of abuse in urine toxicology, accounting for 25.62% of all positive results, this was followed by Cannabis and Amphetamines with 21.67% and 20.20% respectively. The largest age group that presented was between 30-39 inclusive. Benzodiazepines are the most prevalent positive result in drug of abuse screens in Tallaght University Hospital and the 30-39 age group contained the most positives and number of samples sent for toxicology analysis, supporting the claims of recent literature.